Cytotoxic activity induced by the alkaloid extract from Ipomoea carnea on primary murine mixed glial cultures. (December 2020) - Cholich, Luciana Andrea; Pistán, María Elena; Torres, Ana María; Ortega, Hugo Héctor; Gardner, Dale R.; Bustillo, Soledad
Abstract: The prolonged consumption of Ipomoea carnea produces neurologic symptoms in animals and a typical histological lesion, cytoplasmic vacuolization, especially in neurons. The toxic principles of I. carnea are the alkaloids swainsonine and calystegines B1, B2, B3 and C1. In this study, primary brain cultures from newborn mouse containing mixed glial cells were utilized. These cells were exposed to Ipomoea extracts containing between 0 and 250 μM swainsonine for 48 h. Morphological changes were investigated through Phase Contrast microscopy and Rosenfeld's staining. The extract induced cytoplasmic vacuolization in astrocytes and microglia in a dose dependent manner, being more evident when cultures were exposed to 250 μM of swainsonine. In addition, acridine orange staining evidenced an increase in the number of lysosomes in both microglia and astrocytes cells. Consistent with this, scanning electron microscopy also showed that both types of cells presented morphological characteristics of cell activation. Ultrastructurally, cells showed vacuoles filled with amorphous material and surrounded by a single membrane and also multilayer membranes. Taken together, these findings suggest that swainsonine along with calystegines, are probably responsible for the activation of glial cells due to a possible lysosomal dysfunction and therefore intracellular storage. Our results demonstrate that this in vitro glial cell model is a very good alternative to in vivo studies that require several weeks of animal intoxication to observe similar neurotoxic effects. Highlights: Ipomoea carnea alkaloid extract induced morphological and ultrastructural changes in murine mixed glial primary cultures. Alkaloid extract induced cytoplasmic vacuolization and autophagy vacuoles formation due to possible lysosomal dysfunction. Swainsonine and calystegines are mainly responsible for the activation of glial cells due to possible lysosomal dysfunction. In vitro cell model that does not require several weeks of animal intoxication to obtain similar neurotoxic effects.